Komunikasi dalam teori dan praktek - Astrid S. Susanto (Binacipta, 1974)
ws.jl.1.c.1-5, jl.2.c.1-4/ir,jil.1,c.6-7 ; jil.2,c.5-6/ tr, jil. 1=c.9/ir, jil.2,c.7/tr, jil.1=c.10; jil.2=c.8/en, jil.2=c.9/en, jil.1=c.11